Sulfation modification enhances the intestinal regulation of Cyclocarya paliurus polysaccharides in cyclophosphamide-treated mice via restoring intestinal mucosal barrier function and modulating gut microbiota. Issue 24 (25th November 2021) - Yu, Yue; Zhu, Haibin; Shen, Mingyue; Yu, Qiang; Chen, Yi; Xie, Jianhua
Abstract : This work aimed to investigate the effects of a sulfated derivative of Cyclocarya paliurus polysaccharide (SCP3) on cyclophosphamide (CTX)-induced intestinal barrier damage and intestinal microbiota in mice. Abstract : This work aimed to investigate the effects of a sulfated derivative of Cyclocarya paliurus polysaccharide (SCP3) on cyclophosphamide (CTX)-induced intestinal barrier damage and intestinal microbiota in mice. The results showed that SCP3 increased the intestine antioxidant defense, repaired the intestinal barrier via restoring villi length and crypt depth, and up-regulated the expression of tight junction proteins. Bacterial 16S rRNA sequencing results confirmed that SCP3 dramatically altered the structure of the gut microbiota, increased the diversity of gut microbiota, and regulated the relative abundances of specific bacteria, including increasing the abundances of Bacteroidetes, Firmicutes, Tenericutes, Oscillospira, and Akkermansia, and decreasing the abundances of Proteobacteria and Verrucomicrobia . In conclusion, SCP3 can improve intestinal function in CTX-treated mice via enhancing the intestinal oxidative stress capacity, repairing the intestinal mucosal barrier, and regulating intestinal microorganisms, and this study provides a scientific theoretical basis for the application of SCP3 in the food and pharmaceutical fields.